Pengaruh Pemberian Pupuk Kandang dan KCl Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Grace Sera Sartika Sitompul1; Husna Yetti; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research was conducted at experimental farm, the Faculty of Agriculture, Riau University, Campus Bina Widya Km 12,5, sub-district of Simpang Baru, district of Tampan, Pekanbaru, from March until June 2016 to got combination of manure and KCl fertilizer well as best single factor for the growth and production of shallot. The research design was randomized completely block design, factorial 2 x 4 and 3 replications. The first factor was manure (cow manure and chicken manure) and the second factor was KCl fertilizer (0,200,300 and 400 kg.ha-1). Data results were analyzed statistically operates with anova and Duncan test continued level of 5%. Parameter observed were plant height, total of leaves, winding of bulbs, total bulbs/clump, fresh weight of bulbs and dry weight of bulbs. The result revealed that the 20 ton.ha-1 chicken manure with 200 kg.ha-1 KCl fertilizer were the better than another treatments because the treatments showed the highest quality that fresh weight of bulbs (373,5 g.m-2) and dry weight of bulbs (314,4 gr.m-2).  Key word : manure, KCl fertilizer, shallot.